Ideologia colonial portuguesa através dos manuais escolares em África - Carlos Augusto Castelo Branco Filho (2020)
The strength of education resides infact of being a knowledge, ideas and common beliefs producer that characterize a society. African societies always had an educational system, the so-called natural education, focused on survival according to the natural environment, where the accumulated experiences were transmitted from generation to generation throughout the years. There is no direct parallelism between the education and the school. Education exists and always did where there never had existed schools before. In these societies, there were not always a clear separation between who teaches and who is being taught. Education is a fine line that guides discourses as well as practices that determine the future of a nation. It can be used both to consolidate the formation of a society secure of its rights and duties, having in its discourses the force of knowledge, but can also be used to segregate, dominate and manipulate a group of people. In the colonial period, education had been used as a hanger to economically and politically support the colony. Also having as justifiable base the civilization of the natives, considered barbarians. Education, seen as a superstructure, can be said to be the result of various determinations, reinforced by the greed of political and ideological forces of a once dominant government both economically and politically, but also a government I desired moral and intellectual dominion, creating through of education a hegemony of power. The present research will have in its main bias to raise reflections regarding the importance that the education was for the solidification of the colonial system, as well as for the formation of groups and of nations in the post-independence.